2014
DOI: 10.1037/spq0000037
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cognitive strengths and weaknesses: Identification rates, agreement, and validity for learning disabilities identification.

Abstract: Purpose Few empirical investigations have evaluated LD identification methods based on a pattern of cognitive strengths and weaknesses (PSW). This study investigated the reliability and validity of two proposed PSW methods: the concordance/discordance method (C/DM) and cross battery assessment (XBA) method. Methods Cognitive assessment data for 139 adolescents demonstrating inadequate response to intervention was utilized to empirically classify participants as meeting or not meeting PSW LD identification cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 37 publications
2
104
0
Order By: Relevance
“…Validity Miciak et al (2014b) also evaluated the external validity of the identification approaches by comparing the performance of participants that met criteria and participants that did not meet criteria on academic measures which were not utilized to identify groups. Comparisons failed to find meaningful differences in academic performance between emergent subgroups for either method.…”
Section: Approaches Based On Pswmentioning
confidence: 99%
See 1 more Smart Citation
“…Validity Miciak et al (2014b) also evaluated the external validity of the identification approaches by comparing the performance of participants that met criteria and participants that did not meet criteria on academic measures which were not utilized to identify groups. Comparisons failed to find meaningful differences in academic performance between emergent subgroups for either method.…”
Section: Approaches Based On Pswmentioning
confidence: 99%
“…However, all three approaches demonstrated moderate to low sensitivity and very low positive predictive power, because false-positive rates for LD identification were high . Miciak et al (2014b) utilized observed data for a sample of 139 adolescents demonstrating inadequate RTI to empirically classify participants as meeting or not meeting PSW LD identification criteria according to the C/DM and XBA methods. An investigation of the resulting identification decisions permitted an analysis of the identification rates, agreement, and external validity of the two identification approaches.…”
Section: Approaches Based On Pswmentioning
confidence: 99%
“…Furthermore, there was little difference in the academic performance of those who met, or did not meet, the learning disabled criteria, thus posing questions about the external validity of the PSW model. Given these findings, Miciak and his colleagues [45] concluded that it would be difficult to justify the significant resource implications that follow on from widespread use of PSW methods. A similar study, this time with second grade children [46] arrived at broadly similar conclusions.…”
Section: The Resilience Of Discrepancy Testingmentioning
confidence: 99%
“…The additional contribution provided by the cognitive measures did not appear to justify the costs involved. Recent studies [42,45,73] have similarly concluded that there is minimal value in assessing cognitive characteristics for the purpose of predicting how children will respond to intervention. Put simply, the additional information such assessments can provide, above and beyond that yielded by baseline academic assessment or curriculum based or embedded measures [74] appears not to be worth the investment of resources that is required.…”
Section: Predicting Academic Progressmentioning
confidence: 99%
See 1 more Smart Citation